2011
DOI: 10.1016/s1734-1140(11)70393-0
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in experimental seizures and epilepsy

Abstract: Although melatonin is approved only for the treatment of jet-lag syndrome and some types of insomnia, clinical data suggest that it is effective in the adjunctive therapy of osteoporosis, cataract, sepsis, neurodegenerative diseases, hypertension, and even cancer. Melatonin also modulates the electrical activity of neurons by reducing glutamatergic and enhancing GABA-ergic neurotransmission. The indoleamine may also be metabolized to kynurenic acid, an endogenous anticonvulsant. Finally, the hormone and its me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 85 publications
1
53
0
1
Order By: Relevance
“…However, melatonin failed to suppress the development of KA-induced SE both in Wistar rats and SHRs, with results that agree with our previous data demonstrating that the long-term melatonin treatment at a dose of 10 mg/kg after KA-induced SE decreased the latency for onset of the first spontaneous recurrent seizure and attenuated the seizure frequency during the treatment period without preventing the development of chronic epileptic state in Wistar rats and SHRs (Tchekalarova et al, 2013). Although a number of experimental data indicate that acute melatonin injection exerts an anticonvulsant effect in different seizure tests (Banach et al, 2011;de Lima and Soares, 2005), this hormone was suggested only for add-on therapy in epileptic patients with insomnia (Rufo-Campos, 2002). The contradictory literature data concerning the anticonvulsant efficacy of melatonin applied at pharmacological doses are related to its time-, age-and model-dependent effects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, melatonin failed to suppress the development of KA-induced SE both in Wistar rats and SHRs, with results that agree with our previous data demonstrating that the long-term melatonin treatment at a dose of 10 mg/kg after KA-induced SE decreased the latency for onset of the first spontaneous recurrent seizure and attenuated the seizure frequency during the treatment period without preventing the development of chronic epileptic state in Wistar rats and SHRs (Tchekalarova et al, 2013). Although a number of experimental data indicate that acute melatonin injection exerts an anticonvulsant effect in different seizure tests (Banach et al, 2011;de Lima and Soares, 2005), this hormone was suggested only for add-on therapy in epileptic patients with insomnia (Rufo-Campos, 2002). The contradictory literature data concerning the anticonvulsant efficacy of melatonin applied at pharmacological doses are related to its time-, age-and model-dependent effects.…”
Section: Discussionsupporting
confidence: 91%
“…stroke and traumatic brain injury (Chung and Han, 2003) as well as toxic quinones and oxidative stress produced by catecholamines (Hirata et al, 1998). Single injection of melatonin in rats before and during the KA-or pilocarpine-induced status epilepticus (SE) has neuroprotective effect by reducing the neuronal death, supragranular mossy fiber sprouting, lipid peroxidation (LP), and microglial activation (Banach et al, 2011;de Lima and Soares, 2005;Guisti et al, 1996). So far, a broad spectrum of in vitro and in vivo studies confirming the attitude that melatonin behaves as a free radical scavenger and potent antioxidant (Reiter et al, 2007) has been accumulated.…”
Section: Introductionmentioning
confidence: 99%
“…72 Melatonin may specifically inhibit the N-methyl-D-aspartate subtype of excitatory glutamatergic receptors in rat striatum. 73 Moreover, melatonin increases brain g-aminobutyric acid concentrations and receptor affinity 74 and potentiates brain inhibitory transmission via g-aminobutyric acid synapses.…”
Section: Childhood Seizure Disordersmentioning
confidence: 99%
“…3 Melatonin (N-acetyl-5-methoxytryptamine) is secreted mostly at night and in the dark, and exposure to light reduces its secretion. 4 Melatonin seems to possess some anticonvulsant effects [5][6][7][8] ; some studies suggest an association between melatonin and the occurrence of febrile seizures 9-11 also as an explanation to the epidemiology of febrile seizures. 10,11 Many types of epileptic seizure occur according to a specific circadian rhythm.…”
Section: Introductionmentioning
confidence: 99%